Nodular cast iron, casting and preparation method thereof

By defining the composition of ductile iron and adding silicon carbide, the spheroidization rate and pearlite distribution uniformity are improved, the problem of uneven performance of the hardened layer after laser quenching is solved, and the comprehensive performance improvement of the hardened layer and the mechanical performance optimization of the castings are achieved.

CN119685692AActive Publication Date: 2025-03-25GUANGDONG ZHONGTIAN CHUANGZHAN DUCTILE IRON CO LTD

Patent Information

Application Number
CN202411895393.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-21
Publication Date
2025-03-25
Estimated Expiration
2044-12-21

AI Technical Summary

Technical Problem

The prior art After laser quenching, the performance of the hardened layer of the ductile iron is not improved enough, and the performance of the hardened layer is uneven, resulting in a contradiction between the hardness of the casting and the finishing accuracy.

Method used

By limiting the composition of ductile iron, the number and distribution of pearlite are controlled, and silicon carbide is added when the iron liquid is transferred to the electric furnace, and spheroidization and incubation are carried out to improve the spheroidization rate and the number of graphite spheres to ensure that the number of pearlite is between 35-45%.

Benefits of technology

The comprehensive performance improvement of the hardened layer after laser quenching is achieved, and the performance of the hardened layer is relatively uniform, avoiding the problems of casting distortion and uneven hardness, and meeting the mechanical performance needs of downstream industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685692A_ABST
    Figure CN119685692A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nodular cast iron preparation, and discloses nodular cast iron, a casting and a preparation method of the nodular cast iron, and the nodular cast iron comprises the following chemical components in percentage by weight: 3.68 to 3.75 percent of C, 2.35 to 2.45 percent of Si, less than or equal to 0.10 percent of Mn, 0.010 to 0.030 percent of P, 0.008 to 0.015 percent of S, less than or equal to 0.010 percent of Ti, 0.0050 to 0.0060 percent of Sb, 0.050 to 0.060 percent of Sn, 0.0065 to 0.0080 percent of La, 0.035 to 0.045 percent of Mg and the balance of Fe and unremovable impurities. The preparation method of the nodular cast iron comprises the following steps that 1, raw materials are smelted to obtain molten iron; 2, slag pulling is conducted on the molten iron, and impurities are removed; 3, the molten iron obtained in the step 2 is poured into an electric furnace, silicon carbide accounting for 0.20-0.30% of the weight of the molten iron is added in the process, and then spheroidizing inoculation treatment is conducted; and 4, pouring is conducted, nodular cast iron is obtained, and stream inoculation treatment is conducted in the pouring process. By limiting the composition and the dosage of the nodular cast iron and controlling the adding time and the dosage of silicon carbide in the preparation process, pearlites in the nodular cast iron can be uniformly distributed, and the number of the pearlites is stably controlled between 35% and 45%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ductile iron preparation, and in particular to ductile iron, a casting and a preparation method thereof. Background Art

[0002] Laser quenching is a quenching technology that uses laser to heat the material surface to above the phase transition point. As the material itself cools, the austenite transforms into martensite, thereby hardening the material surface.

[0003] Since some castings produced from ductile iron need to meet the requirements of high hardness and high wear resistance, the castings produced from ductile iron can be finished by means of laser quenching to improve their surface hardness and wear resistance, while improving their mechanical properties and surface quality. This treatment method can not only improve the strength and wear resistance of the material, but also retain excellent toughness and plasticity.

[0004] For example, prior art 1: Chinese patent 201510413103.5 discloses a finishing process for a connecting arm and a steering wheel of QT600 ductile iron, and the steps are: stress relief annealing treatment of the casting; rough finishing; normalizing treatment; finishing; composite nitriding treatment of the entire surface of the workpiece; laser quenching treatment of the part with rounded corners of the workpiece; deformation detection; 0.1mm finishing polishing adjustment; the present invention improves the stability and repeatability of the product. The present invention first performs overall nitriding on the product and then performs laser quenching treatment on the rounded corner position, so that the surface of the casting obtains high hardness, while ensuring the original hardness and smoothness of the cast iron, reliable quality, eliminating the internal stress in the casting, reducing the tendency of the rounded corner part of the product to gradually crack, and improving the hardness value of the laser quenching area of ​​the connecting arm and the steering seat, and solving the contradiction between hardness and finishing accuracy. Moreover, since there are not many parts to be laser quenched, there is almost no distortion of the casting after laser quenching.

[0005] The above technology uses laser quenching technology to improve the hardness of ductile iron. However, since it only performs laser quenching on the rounded corners of the product, the demand for increased hardness after laser quenching is not high. Therefore, the existing technology 1 does not conduct in-depth research on improving the performance of the hardened layer formed by laser quenching.

[0006] The study found that the hardened layer obtained after laser quenching is not only related to the process used, but also has a great relationship with the ductile iron itself. For example, the amount of pearlite and ferrite in the ductile iron, as well as the uniformity of pearlite distribution in the ductile iron, have a great impact on the performance of the hardened layer obtained after laser quenching. In order to improve the hardness and wear resistance of the surface of castings produced by ductile iron, it is necessary to develop the corresponding ductile iron, so as to maximize the comprehensive performance of the hardened layer obtained after laser quenching. Summary of the invention

[0007] One of the purposes of the present invention is to provide a ductile iron which not only has excellent mechanical properties but also contains pearlite in a specific content range, the pearlite is evenly distributed, and can maximize the comprehensive performance of the hardened layer obtained after laser quenching.

[0008] Another object of the present invention is to provide a method for preparing a casting, which can fine-process ductile iron according to customer requirements, and then perform laser quenching on the mold surface to obtain a hardened layer with high mechanical properties.

[0009] At the same time, the present invention also provides a casting, which is obtained by sequentially pouring and fine-processing the ductile iron of the present invention. The hardened layer obtained after laser quenching treatment has extremely excellent mechanical properties. Moreover, since the pearlite of the ductile iron is evenly distributed, the performance of each position of the hardened layer can be relatively uniform, and no excessive stress difference will be generated to cause deformation and failure of the casting.

[0010] To achieve the above object, the present invention provides a ductile iron, which comprises the following chemical components in weight percentage: C: 3.68-3.75%, Si: 2.35-2.45%, Mn≤0.10%, P: 0.010-0.030%, S: 0.008-0.015%, Ti≤0.010%, Sb: 0.0050-0.0060%, Sn: 0.050-0.060%, La: 0.0065-0.0080%, Mg: 0.035-0.045%, and the balance is Fe and non-removable impurities;

[0011] The preparation method of ductile iron comprises the following steps:

[0012] Step 1: Smelting the raw materials to obtain molten iron;

[0013] Step 2: Deslagging the molten iron and removing impurities;

[0014] Step 3: Pour the molten iron obtained in step 2 into an electric furnace, add 0.20-0.30% of the weight of the molten iron with silicon carbide, and then perform spheroidization inoculation treatment;

[0015] Step 4: Casting is performed to obtain ductile iron, and inoculation treatment is performed during the casting process.

[0016] The present invention defines the components in ductile iron, mainly as follows: (1) the amount of manganese and copper in ductile iron is controlled to be very low. Since the metal prices of manganese and copper are relatively high, the present invention adopts a technical solution without additionally adding manganese and copper elements, which can effectively control the uniformity and amount of pearlite and reduce production costs; (2) Sb and Sn elements are added to ductile iron and the amount is extremely small, but needs to be strictly controlled.

[0017] Meanwhile, in the preparation process of ductile iron, the present invention is different from the prior art in which silicon carbide is added before or during smelting. In the present invention, a certain amount of silicon carbide is added during the process of transferring the molten iron to the electric furnace.

[0018] The present invention limits the components in ductile iron and delays the time of adding silicon carbide. The two work together to make the ductile iron have a high spheroidization rate, a large number of graphite nodules, a pearlite amount between 35-45%, and a uniform distribution of pearlite; the ductile iron ensures the performance improvement of the hardened layer obtained after laser quenching, while maximizing the comprehensive performance of the hardened layer and making the performance improvement of each part of the hardened layer uniform.

[0019] More preferably, the raw materials in step 1 are pig iron, recycled materials, scrap steel, carburizer, and ferrosilicon.

[0020] Further preferably, the raw materials in step 1 are 20-30% pig iron, 20-30% recycled materials, 40-58% scrap steel, 1.22-2.16% carburizer, and 0.50-1.24% ferrosilicon; and the contents of manganese and titanium in the pig iron, recycled materials and scrap steel must be strictly controlled, that is, Mn≤0.10%, Ti≤0.010%.

[0021] The amount of pearlite in the ductile iron is 35-45%.

[0022] Preferably, the smelting temperature in step 1 is 1460-1500°C.

[0023] Preferably, the specific operation of step 2 is: cooling the molten iron to 1360-1400° C. after slagging.

[0024] Furthermore, the specific operation of step 3 is: pouring the molten iron cooled in step 2 into an electric furnace, adding 0.20-0.30% of the weight of the molten iron with silicon carbide during the process, heating to 1440-1460° C. and then keeping the temperature for 8 minutes to perform spheroidization inoculation treatment.

[0025] Furthermore, in step 3, before the spheroidizing inoculation treatment, 1.2% of the weight of the molten iron by weight of a spheroidizing agent, 0.4% of the weight of the molten iron by weight of a first special-effect inoculant, 0.0056-0.0066% of the weight of the molten iron by weight of Sb, 0.055-0.065% of Sn and 0.15% of crushed steel particles are added to the molten iron after insulation for covering.

[0026] Preferably, the composition of the spheroidizing agent is Mg: 5.52%, Si: 45.5%, La: 0.98%, Ca: 1.75%, Al: 0.44%, and the remaining Fe; the particle size is 5-25 mm;

[0027] Preferably, the first special-effect inoculant has a composition of Si: 74.3%, Ba: 2.25%, Ce: 1.22%, Al: 0.78%, and the remainder Fe, and a particle size of 3-8 mm.

[0028] Furthermore, the specific operation of step 4 is: pouring at 1340-1350° C., and adding 0.1% of the weight of the molten iron as the second special inoculant to perform in-stream inoculation during the pouring process.

[0029] Preferably, the second special-effect inoculant has a composition of Si: 72.1%, Ca: 2.33%, an appropriate amount of S, an appropriate amount of O, Al: 0.46%, and the remainder of Fe, with a particle size of 0.2-0.7 mm.

[0030] The present invention also discloses a method for preparing a casting, comprising the following steps:

[0031] Step a: pouring the ductile iron into a furan resin sand mold and cooling it to obtain a casting;

[0032] Step b: After finishing the die surface of the ingot, laser quenching is performed.

[0033] The finishing process is to perform finishing milling on the die surface of the ingot to meet the dimensional accuracy required by the customer.

[0034] Preferably, the power of the laser quenching treatment is 3000-3200 W, and the scanning speed is 360-390 mm / min.

[0035] The present invention also discloses a casting, which is prepared by the casting preparation method. The casting is subjected to laser quenching treatment to obtain a hardened layer with a thickness of 0.4-0.5 mm and a hardness of 350-400 HBW.

[0036] Beneficial Effects

[0037] Compared with the prior art, the present invention has at least the following advantages:

[0038] (1) The present invention discloses a ductile iron. By limiting the composition and amount of the ductile iron and controlling the addition time and amount of silicon carbide during the preparation process, the pearlite in the ductile iron can be evenly distributed and the amount of pearlite can be stably controlled between 35-45%, and the amount of graphite nodules in the ductile iron can be increased, thereby meeting the requirements of subsequent further laser quenching treatment.

[0039] (2) The casting obtained by fine machining of the ductile iron in the present invention has a hardened layer produced by laser quenching after the die surface is laser quenched, which has excellent mechanical properties and can meet the needs of downstream industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The present invention is further described below in conjunction with the accompanying drawings and embodiments;

[0041] Figure 1 This is a picture of the spheroidization rate of a sample with a thickness of 300 mm prepared in Example 3 of the present invention;

[0042] Figure 2 This is a picture of the amount of pearlite in a sample with a thickness of 300 mm prepared in Example 3 of the present invention;

[0043] Figure 3 This is a picture of the spheroidization rate of a sample with a thickness of 300 mm prepared in Comparative Example 1 of the present invention;

[0044] Figure 4 This is a picture of the amount of pearlite in a sample with a thickness of 300 mm prepared in Comparative Example 2 of the present invention;

[0045] Figure 5 This is a picture of the spheroidization rate of a sample with a thickness of 300 mm prepared in Comparative Example 3 of the present invention;

[0046] Figure 6 This is a picture of the amount of pearlite in a sample with a thickness of 300 mm prepared in Comparative Example 5 of the present invention;

[0047] Figure 7 This is a picture of the amount of pearlite in a sample with a thickness of 300 mm prepared in Comparative Example 6 of the present invention;

[0048] Figure 8 This is a picture of the spheroidization rate of a sample with a thickness of 300 mm prepared in Comparative Example 7 of the present invention;

[0049] Fig. 9 It is a front view of the castings of application examples 1 and 2 of the present invention;

[0050] Fig.10 is a bottom view of the castings of Application Examples 1 and 2 of the present invention;

[0051] Fig.11 is a top view of the castings of application examples 1 and 2 of the present invention;

[0052] Fig.12 It is a left side view of the castings of application examples 1 and 2 of the present invention;

[0053] Fig.13 It is a stereoscopic view of the castings of Application Examples 1 and 2 of the present invention. DETAILED DESCRIPTION

[0054] The present invention will be further described below in conjunction with the embodiments, but it does not constitute any limitation to the present invention. Any limited number of modifications made within the scope of the claims of the present invention are still within the scope of the claims of the present invention.

[0055] In order to explain the technical content of the present invention in detail, further description is given below in conjunction with the implementation modes.

[0056] In the following examples and comparative examples, the composition of the spheroidizer is Mg: 5.52%, Si: 45.5%, La: 0.98%, Ca: 1.75%, Al: 0.44%, and Fe; the particle size is 5-25mm; the composition of the first special inoculant is Si: 74.3%, Ba: 2.25%, Ce: 1.22%, Al: 0.78%, and Fe; the particle size is 3-8mm; the composition of the second special inoculant is Si: 72.1%, Ca: 2.33%, S is appropriate, O is appropriate, Al: 0.46%, and Fe is appropriate, and the particle size is 0.2-0.7mm; the composition of silicon carbide is: SiC: 93% (Si: 65%, C: 28%), Fe 2 O 3 : 1.2%,Al 2 O 3 : 1.1%, residual Fe, particle size: 1-5mm; Antimony (Sb) comes from 99.95% antimony particles crushed into 1-5mm particle size, and the absorption rate at 1440-1460℃ is 91%; Tin (Sn) comes from 99.92% tin particles with a particle size of 3-10mm, and the absorption rate at 1440-1460℃ is 92%.

[0057] In the following examples and comparative examples, unless otherwise specified, the % is percentage by weight.

[0058] Example 1

[0059] A ductile iron is prepared by the following steps:

[0060] Step 1: Smelting pig iron, recycled materials, scrap steel, carburizer and ferrosilicon at a temperature of 1460° C. to obtain molten iron;

[0061] Step 2: After slagging, cool the molten iron to 1360°C;

[0062] Step 3: pour the molten iron cooled in step 2 into an electric furnace, add 0.20% silicon carbide by weight of the molten iron in the process, heat to 1450°C and keep warm for 8 minutes, then add 1.2% spheroidizing agent by weight of the molten iron, 0.4% first special inoculant by weight of the molten iron, 0.0058% Sb by weight of the molten iron, 0.062% Sn by weight of the molten iron and 0.15% crushed steel grains by weight of the molten iron to cover, and perform spheroidization inoculation treatment;

[0063] Step 4: pouring at 1345° C., adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0064] Sampling was taken after pouring, and the chemical composition of the ductile iron was: C: 3.68%, Si: 2.42%, Mn: 0.08%, P: 0.018%, S: 0.011%, Ti: 0.007%, Sb: 0.0053%, Sn: 0.057%, La: 0.0071%, Mg: 0.035%, and the remainder was Fe and non-removable impurities.

[0065] Example 2

[0066] A ductile iron is prepared by the following steps:

[0067] Step 1: Smelting pig iron, recycled materials, scrap steel, carburizer and ferrosilicon at a temperature of 1460° C. to obtain molten iron;

[0068] Step 2: After slagging, cool the molten iron to 1360°C;

[0069] Step 3: pour the molten iron cooled in step 2 into an electric furnace, add 0.20% of the weight of the molten iron with silicon carbide in the process, heat to 1450°C and keep warm for 8 minutes, then add 1.2% of the weight of the molten iron with a spheroidizing agent, 0.4% of the weight of the molten iron with a first special inoculant, 0.0061% of the weight of the molten iron with Sb, 0.059% of the weight of the molten iron with Sn and 0.15% of the weight of the molten iron with crushed steel particles for spheroidization inoculation treatment;

[0070] Step 4: pouring at 1342° C., adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0071] Sampling was taken after pouring, and the chemical composition of the ductile iron was: C: 3.71%, Si: 2.38%, Mn: 0.07%, P: 0.011%, S: 0.015%, Ti: 0.009%, Sb: 0.0055%, Sn: 0.054%, La: 0.0068%, Mg: 0.036%, and the remainder was Fe and non-removable impurities.

[0072] Example 3

[0073] A ductile iron is prepared by the following steps:

[0074] Step 1: Smelting pig iron, recycled materials, scrap steel, carburizer and ferrosilicon at a temperature of 1460° C. to obtain molten iron;

[0075] Step 2: After slagging, cool the molten iron to 1360°C;

[0076] Step 3: pour the molten iron cooled in step 2 into an electric furnace, add 0.30% of the weight of the molten iron with silicon carbide in the process, heat to 1450°C and keep warm for 8 minutes, then add 1.2% of the weight of the molten iron with a spheroidizing agent, 0.4% of the weight of the molten iron with a first special inoculant, 0.0066% of the weight of the molten iron with Sb, 0.062% of the weight of the molten iron with Sn and 0.15% of the weight of the molten iron with crushed steel particles for spheroidization inoculation treatment;

[0077] Step 4: pouring at 1348°C, adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0078] Sampling was taken after pouring, and the chemical composition of the ductile iron was: C: 3.75%, Si: 2.44%, Mn: 0.088%, P: 0.028%, S: 0.011%, Ti: 0.010%, Sb: 0.0060%, Sn: 0.057%, La: 0.0065%, Mg: 0.040%, and the remainder was Fe and non-removable impurities.

[0079] Example 4

[0080] A ductile iron is prepared by the following steps:

[0081] Step 1: Smelting pig iron, recycled materials, scrap steel, carburizer and ferrosilicon at a temperature of 1460° C. to obtain molten iron;

[0082] Step 2: After slagging, cool the molten iron to 1360°C;

[0083] Step 3: pour the molten iron cooled in step 2 into an electric furnace, add 0.25% of the weight of the molten iron with silicon carbide in the process, heat to 1450°C and keep warm for 8 minutes, then add 1.2% of the weight of the molten iron with a spheroidizing agent, 0.4% of the weight of the molten iron with a first special inoculant, 0.0065% of the weight of the molten iron with Sb, 0.060% of the weight of the molten iron with Sn and 0.15% of the weight of the molten iron with crushed steel particles for spheroidization inoculation treatment;

[0084] Step 4: pouring at 1350° C., adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0085] Sampling was taken after pouring, and the chemical composition of the ductile iron was: C: 3.72%, Si: 2.40%, Mn: 0.076%, P: 0.010%, S: 0.013%, Ti: 0.005%, Sb: 0.0059%, Sn: 0.055%, La: 0.0077%, Mg: 0.041%, and the remainder was Fe and non-removable impurities.

[0086] Comparative Example 1

[0087] A ductile iron is prepared by the following steps:

[0088] Step 1: Smelting pig iron, recycled materials, scrap steel, carburizer and ferrosilicon at a temperature of 1460° C. to obtain molten iron;

[0089] Step 2: After slagging, cool the molten iron to 1360°C;

[0090] Step 3: pour the molten iron cooled in step 2 into an electric furnace, add 0.20% of the weight of the molten iron with silicon carbide in the process, heat to 1450°C and keep warm for 8 minutes, then add 1.2% of the weight of the molten iron with a spheroidizing agent, 0.4% of the weight of the molten iron with a first special inoculant, 0.062% of the weight of the molten iron with Sn and 0.15% of the weight of the molten iron with crushed steel particles for spheroidizing and inoculating treatment;

[0091] Step 4: pouring at 1344° C., adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0092] Sampling was performed after pouring, and the chemical composition of the ductile iron was as follows: C: 3.75%, Si: 2.45%, Mn: 0.083%, P: 0.026%, S: 0.013%, Ti: 0.009%, Sn: 0.057%, La: 0.0067%, Mg: 0.038%, and the remainder was Fe and non-removable impurities.

[0093] Comparative Example 2

[0094] A ductile iron is prepared by the following steps:

[0095] Step 1: Smelting pig iron, recycled materials, scrap steel, carburizer and ferrosilicon at a temperature of 1460° C. to obtain molten iron;

[0096] Step 2: After slagging, cool the molten iron to 1360°C;

[0097] Step 3: pour the cooled molten iron in step 2 into an electric furnace, add 0.20% silicon carbide by weight of the molten iron in the process, heat to 1450°C and keep warm for 8 minutes, then add 1.2% spheroidizing agent by weight of the molten iron, 0.4% first special inoculant by weight of the molten iron, 0.0066% Sb by weight of the molten iron and 0.15% crushed steel grains by weight of the molten iron to cover, and perform spheroidization inoculation treatment;

[0098] Step 4: pouring at 1345° C., adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0099] Sampling was performed after pouring, and the chemical composition of the ductile iron was as follows: C: 3.73%, Si: 2.42%, Mn: 0.079%, P: 0.025%, S: 0.014%, Ti: 0.007%, Sb: 0.0060%, La: 0.0071%, Mg: 0.038%, and the remainder was Fe and non-removable impurities.

[0100] Comparative Example 3

[0101] A ductile iron is prepared by the following steps:

[0102] Step 1: Smelting pig iron, recycled materials, scrap steel, carburizer and ferrosilicon at a temperature of 1460° C. to obtain molten iron;

[0103] Step 2: After slagging, cool the molten iron to 1360°C;

[0104] Step 3: pour the molten iron cooled in step 2 into an electric furnace, add 0.20% of the weight of the molten iron with silicon carbide in the process, heat to 1450°C and keep warm for 8 minutes, then add 1.2% of the weight of the molten iron with a spheroidizing agent, 0.4% of the weight of the molten iron with a first special inoculant, 0.0046% of the weight of the molten iron with Sb, 0.062% of the weight of the molten iron with Sn and 0.15% of the weight of the molten iron with crushed steel particles for spheroidizing and inoculating treatment;

[0105] Step 4: pouring at 1346°C, adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0106] Sampling was taken after pouring, and the chemical composition of the ductile iron was: C: 3.69%, Si: 2.45%, Mn: 0.086%, P: 0.030%, S: 0.008%, Ti: 0.008%, Sb: 0.0042%, Sn: 0.057%, La: 0.0066%, Mg: 0.042%, and the remainder was Fe and non-removable impurities.

[0107] Comparative Example 4

[0108] A ductile iron is prepared by the following steps:

[0109] Step 1: Smelting pig iron, recycled materials, scrap steel, carburizer and ferrosilicon at a temperature of 1460° C. to obtain molten iron;

[0110] Step 2: After slagging, cool the molten iron to 1360°C;

[0111] Step 3: pour the molten iron cooled in step 2 into an electric furnace, add 0.20% of the weight of the molten iron with silicon carbide in the process, heat to 1450°C and keep warm for 8 minutes, then add 1.2% of the weight of the molten iron with a spheroidizing agent, 0.4% of the weight of the molten iron with a first special inoculant, 0.0070% of the weight of the molten iron with Sb, 0.062% of the weight of the molten iron with Sn and 0.15% of the weight of the molten iron with crushed steel particles for spheroidization inoculation treatment;

[0112] Step 4: pouring at 1348°C, adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0113] Sampling was taken after pouring, and the chemical composition of the ductile iron was: C: 3.70%, Si: 2.37%, Mn: 0.083%, P: 0.024%, S: 0.012%, Ti: 0.010%, Sb: 0.0064%, Sn: 0.057%, La: 0.0074%, Mg: 0.045%, and the remainder was Fe and non-removable impurities.

[0114] Comparative Example 5

[0115] A ductile iron is prepared by the following steps:

[0116] Step 1: Smelting pig iron, recycled materials, scrap steel, carburizer and ferrosilicon at a temperature of 1460° C. to obtain molten iron;

[0117] Step 2: After slagging, cool the molten iron to 1360°C;

[0118] Step 3: pour the molten iron cooled in step 2 into an electric furnace, add 0.20% silicon carbide by weight of the molten iron in the process, heat to 1450°C and keep warm for 8 minutes, then add 1.2% spheroidizing agent by weight of the molten iron, 0.4% first special inoculant by weight of the molten iron, 0.0066% Sb by weight of the molten iron, 0.044% Sn by weight of the molten iron and 0.15% crushed steel grains by weight of the molten iron to cover, and perform spheroidization inoculation treatment;

[0119] Step 4: pouring at 1350° C., adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0120] Sampling was taken after pouring, and the chemical composition of the ductile iron was: C: 3.74%, Si: 2.35%, Mn: 0.080%, P: 0.022%, S: 0.008%, Ti: 0.009%, Sb: 0.0060%, Sn: 0.040%, La: 0.0067%, Mg: 0.044%, and the remainder was Fe and non-removable impurities.

[0121] Comparative Example 6

[0122] A ductile iron is prepared by the following steps:

[0123] Step 1: Smelting pig iron, recycled materials, scrap steel, carburizer and ferrosilicon at a temperature of 1460° C. to obtain molten iron;

[0124] Step 2: After slagging, cool the molten iron to 1360°C;

[0125] Step 3: pour the molten iron cooled in step 2 into an electric furnace, add 0.20% of the weight of the molten iron with silicon carbide in the process, heat to 1450°C and keep warm for 8 minutes, then add 1.2% of the weight of the molten iron with a spheroidizing agent, 0.4% of the weight of the molten iron with a first special inoculant, 0.0066% of the weight of the molten iron with Sb, 0.071% of the weight of the molten iron with Sn and 0.15% of the weight of the molten iron with crushed steel particles for spheroidization inoculation treatment;

[0126] Step 4: pouring at 1340° C., adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0127] Sampling was taken after pouring, and the chemical composition of the ductile iron was: C: 3.71%, Si: 2.45%, Mn: 0.083%, P: 0.029%, S: 0.012%, Ti: 0.007%, Sb: 0.0060%, Sn: 0.065%, La: 0.0069%, Mg: 0.039%, and the remainder was Fe and non-removable impurities.

[0128] Comparative Example 7

[0129] A ductile iron is prepared by the following steps:

[0130] Step 1: Smelting pig iron, recycled materials, scrap steel, carburizer, and ferrosilicon at a temperature of 1460° C. to obtain molten iron, and adding 0.30% silicon carbide based on the total weight of pig iron, recycled materials, scrap steel, carburizer, and ferrosilicon when at least 50% of the solid is melted into molten iron during the smelting process;

[0131] Step 2: After slagging, cool the molten iron to 1360°C;

[0132] Step 3: Pour the molten iron cooled in step 2 into an electric furnace, heat it to 1450°C, add 1.2% of the weight of the molten iron, a spheroidizing agent, 0.4% of the weight of the molten iron, a first special inoculant, 0.0066% of the weight of the molten iron, 0.062% of the weight of the molten iron, Sn and 0.15% of the weight of the molten iron, and cover with crushed steel particles for spheroidization inoculation treatment;

[0133] Step 4: pouring at 1344° C., adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0134] Sampling was taken after pouring, and the chemical composition of the ductile iron was: C: 3.73%, Si: 2.42%, Mn: 0.092%, P: 0.029%, S: 0.013%, Ti: 0.009%, Sb: 0.0060%, Sn: 0.057%, La: 0.0074%, Mg: 0.042%, and the remainder was Fe and non-removable impurities.

[0135] Comparative Example 8

[0136] A ductile iron is prepared by the following steps:

[0137] Step 1: Smelting pig iron, recycled materials, scrap steel, recarburizer, ferrosilicon and silicon carbide at a temperature of 1460° C. to obtain molten iron, wherein the amount of silicon carbide added is 0.3% of the total weight of the pig iron, recycled materials, scrap steel, recarburizer and ferrosilicon;

[0138] Step 2: After slagging, cool the molten iron to 1360°C;

[0139] Step 3: Pour the molten iron cooled in step 2 into an electric furnace, heat it to 1450°C, add 1.2% of the weight of the molten iron, a spheroidizing agent, 0.4% of the weight of the molten iron, a first special inoculant, 0.0066% of the weight of the molten iron, 0.062% of the weight of the molten iron, Sn and 0.15% of the weight of the molten iron, and cover with crushed steel particles for spheroidization inoculation treatment;

[0140] Step 4: pouring at 1349° C., adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process;

[0141] Sampling was taken after pouring, and the chemical composition of the ductile iron was: C: 3.73%, Si: 2.42%, Mn: 0.079%, P: 0.014%, S: 0.007%, Ti: 0.006%, Sb: 0.0060%, Sn: 0.057%, La: 0.0071%, Mg: 0.041%, and the remainder was Fe and non-removable impurities.

[0142] The ductile iron obtained in Examples 1-4 and Comparative Examples 1-8 was cast into samples with a thickness of 70 mm and 300 mm respectively (length and width were both 400 mm×400 mm), and the center point was taken to perform metallographic microscope detection and analysis of the metallographic structure to obtain the spheroidization rate and the amount of pearlite;

[0143] The results show that the spheroidization rate of the samples with thickness of 70 mm and 300 mm prepared in Examples 1-4 and the spheroidization rate of the samples with thickness of 70 mm prepared in Comparative Examples 1-8 are all greater than 92%, and the number of graphite balls is greater than 400 / mm. 2 And the amount of pearlite is greater than 35%;

[0144] The spheroidization rate and the amount of pearlite obtained by metallographic analysis of the center point of the sample with a thickness of 300 mm prepared in Example 3 are shown in Table 1. Figure 1 and Figure 2 .

[0145] Comparative Example 1 The spheroidization rate obtained by metallographic structure analysis of the center point of the sample with a thickness of 300 mm is shown in Figure 3 .

[0146] Comparative Example 2 The amount of pearlite obtained by metallographic structure analysis of the center point of a sample with a thickness of 300 mm is shown in Figure 4 .

[0147] Comparative Example 3: The spheroidization rate obtained by metallographic structure analysis of the center point of the sample with a thickness of 300 mm is shown in Figure 5 .

[0148] Comparative Example 5 The amount of pearlite obtained by metallographic structure analysis of the center point of a sample with a thickness of 300 mm is shown in Figure 6 .

[0149] Comparative Example 6 The amount of pearlite obtained by metallographic structure analysis of the center point of a sample with a thickness of 300 mm is shown in Figure 7 .

[0150] Comparative Example 7 The spheroidization rate obtained by metallographic structure analysis of the center point of the sample with a thickness of 300 mm is shown in Figure 8 .

[0151] However, compared with the sample with a thickness of 300 mm prepared in Example 3, the spheroidization rate of the sample with a thickness of 300 mm prepared in Comparative Examples 1 and 3 is greatly reduced, and the number of graphite nodules is also greatly reduced; the number of pearlite in the sample with a thickness of 300 mm prepared in Comparative Examples 2 and 5 is greatly reduced; and the number of pearlite in the sample with a thickness of 300 mm prepared in Comparative Examples 4 and 6 is increased, and the number of pearlite is greater than 45%, but due to the excessively high Sb or Sn content, the spheroidization rate is greatly reduced, and the spheroidization rate is all lower than 86%, and the number of graphite nodules is also reduced; the number of pearlite in the sample with a thickness of 300 mm prepared in Comparative Examples 7 and 8 does not change much, but due to the wrong timing of adding silicon carbide, the spheroidization rate is reduced, and is all lower than 89%, and the number of graphite nodules is greatly reduced compared with Example 3.

[0152] It can be seen that the present invention can prepare castings with high thickness, high spheroidization rate, large number of graphite nodules and pearlite maintained at 35-45% by controlling the composition and content of ductile iron, especially by controlling the content of antimony and tin, and coordinating the timing and amount of adding silicon carbide during the preparation process.

[0153] In particular, the control of the amount of pearlite, the technical solution of the present invention can make the pearlite of the sample with a thickness of 300mm uniformly distributed by controlling the content of antimony and tin in ductile iron, the timing and amount of adding silicon carbide during the preparation process;

[0154] The four corners and the center of the sample blocks with a thickness of 300 mm prepared in Examples 1-4 and Comparative Examples 1-8 were tested by metallographic microscope to obtain the amount of pearlite, as shown in Table 1, where point 1 is the test point at the upper left corner, point 2 is the test point at the upper right corner, point 3 is the test point at the lower left corner, point 4 is the test point at the lower right corner, and point 5 is the test point at the center;

[0155] Table 1 Test results of pearlite uniformity of samples with a thickness of 300 mm prepared in Examples 1-4 and Comparative Examples 1-8

[0156]

[0157]

[0158] According to the results in Table 1, we can see that:

[0159] According to Examples 1-4, it can be seen that the thick casting obtained by pouring ductile iron of the present invention has the advantages of high spheroidization rate, uniform pearlite distribution and the amount of pearlite controlled between 35-45%.

[0160] According to the data comparison between Example 3 and Comparative Examples 1 and 3, it can be seen that the spheroidization rate of Comparative Examples 1 and 3 is significantly reduced due to the lack of Sb or insufficient Sb content. Although the amount of pearlite has not decreased significantly, the uniformity of pearlite distribution at each point has decreased.

[0161] According to the data comparison between Example 3 and Comparative Examples 2 and 5, it can be seen that in the absence of Sn or too little Sn content, the uniformity and quantity of pearlite will be greatly reduced.

[0162] According to the data comparison between Example 3 and Comparative Examples 4 and 6, the present invention can effectively balance and improve the spheroidization rate by controlling the contents of Sb and Sn, and ensure that the amount of pearlite is between 35-45% and is evenly distributed.

[0163] According to the data comparison between Example 3 and Comparative Examples 7 and 8, it can be seen that the present invention can instantly increase the nucleation core of the molten iron and improve the spheroidization rate by controlling the timing and amount of adding silicon carbide, and can effectively improve the spheroidization rate of the casting and improve the uniformity of pearlite distribution.

[0164] Laser quenching process test:

[0165] The samples with a thickness of 300 mm prepared in Example 3 were treated by the following laser quenching process to obtain samples 1-6 with hardened layers on the surface;

[0166] Sample 1: laser quenching power 3000W, scanning speed 390mm / min;

[0167] Sample 2: laser quenching power 3200W, scanning speed 360mm / min;

[0168] Sample 3: laser quenching power 3200W, scanning speed 320mm / min;

[0169] Sample 4: laser quenching power 3200W, scanning speed 420mm / min;

[0170] Sample 5: laser quenching power 2800W, scanning speed 360mm / min;

[0171] Sample 6: Laser quenching power 3500W, scanning speed 360mm / min.

[0172] The hardness of the surface hardened layer of samples 1-6 was tested at the four corners and the center using the above test method. The results are shown in Table 2:

[0173] Table 2 Hardness results of hardened layer obtained by different laser quenching processes

[0174]

[0175] According to the results in Table 2, when the power of laser quenching treatment is 3000-3200W and the scanning speed is 360-390mm / min, the hardness of the hardened layer is within 350-400HBW, and the hardness difference is less than 15HBW; when the laser quenching power is low or the scanning speed is fast, the hardness of the hardened layer is lower than 350HBW, and the hardness difference is greater than 15HBW; when the laser quenching power is high or the scanning speed is slow, the hardness of the hardened layer is lower than 400HBW, and the hardness difference is greater than 15HBW.

[0176] The laser quenching process of sample 2 was used to laser quench the sample blocks with a thickness of 300 mm prepared in comparative examples 1-8, and then the hardness was tested at the four corners and the center using the above test method. The results are shown in Table 3;

[0177] Table 3 Hardness results of laser quenching hardened layer of samples with a thickness of 300 mm prepared in Comparative Examples 1-8

[0178]

[0179] According to the data of sample 2 in Table 2 and the data in Table 3, it can be seen that:

[0180] When the Sb content is absent or too low, the spheroidization rate is lower than 92%, the number of graphite nodules is less than 400 per mm 2 and the pearlite content is less than 35%, the hardness of the hardened layer is lower than 350 HBW, and the hardness difference is greater than 15 HBW. Good results cannot be achieved, and customer requirements cannot be met.

[0181] Application Example 1

[0182] A casting is poured into a furan resin sand mold using the steps of Example 3 to obtain Figure 9-13 a casting with a casting material of QT500-7A, a casting weight of 12,880 kg, a casting external dimension of 2,032 mm × 2,021 mm × 1,095 mm, and a mold surface wall thickness of 328 mm;

[0183] The mechanical properties of the casting are tested at the four corners and the center using the same testing method as above, and the results are as follows:

[0184] The hardness (HBW) of the casting mold surface: Point 1: 185, Point 2: 188, Point 3: 191, Point 4: 188, Point 5: 192, spheroidization rate: 95%, number of graphite nodules: 500 per mm 2 , pearlite content: 42%, ferrite content: the balance;

[0185] The mechanical properties of the casting body sample (a sample with a diameter of 24 mm and a length of 328 mm is taken from the mold surface thickness and the center part): Tensile strength R m : 462 MPa, yield strength R P0.2 : 327 MPa, elongation A: 6.0%. These mechanical property results are significantly better than the mechanical property guiding value table C1 in Appendix C of "Ductile Iron Castings" GB / T 1348-2019 for the casting body sample of the material grade QT500-7 / C with a casting wall thickness t: 60 < t ≤ 200, where the tensile strength R m (min) 400 MPa, yield strength R P0.2 (min): 260 MPa, elongation A(min): 3%.

[0186] The mold surface of the casting ( Fig.10 ) is laser quenched using a laser quenching power of 3,200 W and a scanning speed of 360 mm / min, and finally a hardened layer with a thickness of 0.46 mm is obtained. After testing, the hardness (HBW) of the hardened layer is Point 1: 382, Point 2: 385, Point 3: 380, Point 4: 388, Point 5: 381.

[0187] Application Example 2

[0188] A casting is poured into a furan resin sand mold using the steps of Example 3 to obtain Figure 9-13The casting, with the casting material being QT500-7A, casting weight: 15850 kg, casting external dimensions: 2193 mm × 2250 mm × 1245 mm, die surface wall thickness: 372 mm;

[0189] Mechanical property tests were conducted on the casting, and the results are as follows:

[0190] Hardness (HBW) of the casting die surface: Point 1: 179, Point 2: 178, Point 3: 183, Point 4: 176, Point 5: 181, spheroidization rate: 93%, number of graphite balls: 400 pieces / mm 2 , pearlite quantity: 40%, ferrite quantity: the balance;

[0191] Mechanical properties of the casting body sample (taking a sample with a diameter of 24 mm and a length of 372 mm from the die surface thickness and the central part): Tensile strength R m : 455 MPa, yield strength R P0.2 : 318 MPa, elongation A: 6.5%. These mechanical property results are significantly better than the mechanical property guiding value table C1 in Appendix C of "Ductile Iron Castings" GB / T 1348-2019 for the casting body sample, where for the material grade QT500-7 / C and casting wall thickness t: 60 < t ≤ 200, the guiding values of tensile strength R m (min) 400 MPa, yield strength R P0.2 (min): 260 MPa, elongation A (min): 3%.

[0192] Laser quenching was carried out on the die surface of the casting ( Fig.10 ) with a laser quenching power of 3200 W and a scanning speed of 360 mm / min, and finally a hardened layer with a thickness of 0.48 mm was obtained. After testing, the hardness (HBW) of the hardened layer is Point 1: 372, Point 2: 370, Point 3: 379, Point 4: 372, Point 5: 369.

[0193] The embodiments presented in this article are only implementation manners selected according to combinations of all possible embodiments. The appended claims should not be limited by the embodiments illustrating the present invention. Some numerical ranges used in the claims include sub-ranges within them, and variations within these ranges should also be covered by the appended claims.

Claims

1. A ductile iron, characterized in that: The ductile iron comprises the following chemical components in weight percentage: C: 3.68-3.75%, Si: 2.35-2.45%, Mn≤0.10%, P: 0.010-0.030%, S: 0.008-0.015%, Ti≤0.010%, Sb: 0.0050-0.0060%, Sn: 0.050-0.060%, La: 0.0065-0.0080%, Mg: 0.035-0.045%, and the balance is Fe and non-removable impurities; The preparation method of ductile iron comprises the following steps: Step 1: Smelting the raw materials to obtain molten iron; Step 2: Deslagging the molten iron and removing impurities; Step 3: Pour the molten iron obtained in step 2 into an electric furnace, add 0.20-0.30% of the weight of the molten iron with silicon carbide, and then perform spheroidization inoculation treatment; Step 4: Casting is performed to obtain ductile iron, and inoculation treatment is performed during the casting process.

2. The ductile iron according to claim 1, characterized in that: The amount of pearlite in the ductile iron is 35-45%.

3. The ductile iron according to claim 1, characterized in that: The smelting temperature of step 1 is 1460-1500°C.

4. The ductile iron according to claim 3, characterized in that: The specific operation of step 2 is: cooling the molten iron to 1360-1400°C after slagging.

5. The ductile iron according to claim 1, characterized in that: The specific operation of step 3 is: pouring the molten iron cooled in step 2 into the electric furnace, adding 0.20-0.30% of the weight of the molten iron with silicon carbide during the process, heating to 1440-1460° C. and then keeping the temperature for 8 minutes to perform spheroidization inoculation treatment.

6. The ductile iron according to claim 5, characterized in that: In step 3, before the spheroidizing inoculation treatment, 1.2% of the weight of the molten iron is used as a spheroidizing agent, 0.4% of the weight of the molten iron is used as a first special inoculant, 0.0056-0.0066% of the weight of the molten iron is used as Sb, 0.055-0.065% of the weight of the molten iron is used as Sn, and 0.15% of crushed steel particles are added to the molten iron after heat preservation to cover the molten iron.

7. The ductile iron according to claim 1, characterized in that: The specific operation of step 4 is: pouring at 1340-1350° C., adding 0.1% of the weight of the molten iron into the second special inoculant for inoculation during the pouring process.

8. A method for preparing a casting, characterized in that: The steps include: Step a: pouring the ductile iron according to any one of claims 1 to 7 into a furan resin sand mold and cooling it to obtain a casting; Step b: After finishing the die surface of the ingot, laser quenching is performed.

9. The method for preparing a casting according to claim 8, characterized in that: The power of the laser quenching treatment is 3000-3200W, and the scanning speed is 360-390mm / min.

10. A casting, characterized in that: The casting is prepared by the method for preparing the casting as claimed in claim 8 or 9, wherein the casting has a hardened layer with a thickness of 0.4-0.5 mm and a hardness of 350-400 HBW after laser quenching treatment.

Citation Information

Patent Citations

  • Machining process for QT-600 ductile iron connecting arms and steering wheels

    CN106702392B

  • Large-section nodular cast iron

    CN102373365A

  • High-strength and high-rigidity ductile cast iron material for compressor and application of ductile cast iron

    CN104264033A

  • Preparation method of spheroidal graphite cast iron

    CN105349873A

  • Nodular cast iron material and preparation method thereof

    CN106191640A

Cited By

  • Aluminum alloy die-casting plunger head material matched with H13 charging barrel in thermal expansion coefficient and preparation method of aluminum alloy die-casting plunger head material

    CN122168969A

  • An aluminum alloy die-cast plunger material with a thermal expansion coefficient matching that of an H13 barrel and its preparation method.

    CN122168969B